2018
DOI: 10.3390/w10050642
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multi-Satellite Precipitation Products for Streamflow Simulations: A Case Study for the Han River Basin in the Korean Peninsula, East Asia

Abstract: The accuracy and sufficiency of precipitation data play a key role in environmental research and hydrological models. They have a significant effect on the simulation results of hydrological models; therefore, reliable hydrological simulation in data-scarce areas is a challenging task. Advanced techniques can be utilized to improve the accuracy of satellite-derived rainfall data, which can be used to overcome the problem of data scarcity. Our study aims to (1) assess the accuracy of different satellite precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 60 publications
(31 reference statements)
2
42
0
Order By: Relevance
“…Although the CMADS data have been applied worldwide since its release in 2016, the application of CMADS in abundant rainfall areas in southern China is lacking [30]. Further investigations of the applicability of the CMADS in the SWAT model are needed to better understand and evaluate the accuracy and efficacy of the dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Although the CMADS data have been applied worldwide since its release in 2016, the application of CMADS in abundant rainfall areas in southern China is lacking [30]. Further investigations of the applicability of the CMADS in the SWAT model are needed to better understand and evaluate the accuracy and efficacy of the dataset.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better reflect the spatial distribution of precipitation, the China Meteorological Assimilation Driving Datasets for the SWAT model version 1.0 (CMADS V1.0) was introduced in this study [50]. The CMADS was developed by Dr. Xianyong Meng from the China Institute of Water Resources and Hydropower Research (IWHR) and has received worldwide attention [28][29][30]. In the CMADS, the integration of air temperature, air pressure, humidity, and wind velocity data were mainly achieved through the LAPS (Local Analysis and Prediction System)/STMAS (Space-Time Multiscale Analysis System).…”
Section: Data Collectionmentioning
confidence: 99%
“…Based on this method, several products have been developed and widely applied in hydrological modeling [26,27]. The China Meteorological Assimilation Driving Datasets for the SWAT model (CMADS), which was developed by Dr. Xianyong Meng from the China Institute of Water Resources and Hydropower Research (IWHR), is one such product and has been widely applied in numerous studies [28][29][30][31]. For example, Liu [28] found that CMADS had unique advantages in hydrological simulations compared with observed data and Climate Forecast System Reanalysis (CFSR).…”
Section: Introductionmentioning
confidence: 99%
“…We examined the performance of TRMA-3B42V7 and CMADS using the six statistical measures (PC, POD, FBI, FAR, CSI and HSS) through the pixel-to-point comparison with the ground-based data. Following the studies of Dai [67] and Vu et al [24], a minimum precipitation threshold of 1.0 mm per day was used for the precipitation and non-precipitation event for ground observation and satellite/reanalysis estimate. The contingency statistics of TRMA-3B42V7 and CMADS were evaluated each year through the precipitation datasets from 2008 to 2016.…”
Section: Precipitation Detectionmentioning
confidence: 99%